دور حوكمة الشركات في تحقيق الإصلاح الإداري (دراسة ميدانية على الشركة السورية للاتصالات في طرطوس) - عبد الرحمن, نسرين; عطية, هنادي; موسى, جوزيف (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This research aimed to identify the role of corporate governance in achieving the administrative reform in the Syrian telecommunications company in Tartous, The research sample consisted of number of employees from top and middle administrative levels in the Syrian telecommunications company in Tartous, and the study based on the stratified random sample and the descriptive approach in the theoretical section and the method of statistical survey in the field study was also adopted. The main results of this research is: existence of strong direct relationship between corporate governance and achieving administrative reform, and also existence direct relationship between dimensions of corporate governance (disclosure and transparency, supervision and control, and moral behavior) and achieving administrative reform, the results confirmed that the strongest relationships between dimensions of corporate governance and administrative reform was relationship between the disclosure and transparency and administrative reform, then relationship between supervision and control and administrative reform. while the relationship between moral behavior and administrative reform was weak and in last place. هدف هذا البحث إلى التعرّف على دور تطبيق حوكمة الشركات في تحقيق الإصلاح الإداري في الشركة السورية للاتصالات في طرطوس، حيث تمثلت عينة البحث بعدد من العاملين في المستويات الإدارية العليا والوسطى في الشركة السورية للاتصالات في طرطوس، وقد تمّ الاعتماد على عينة عشوائية بسيطة، كما تمّ الاعتماد على المنهج الوصفي في القسم النظري وعلى أسلوب المسح الإحصائي في الدراسة الميدانية، وتوصل البحث إلى مجموعة من النتائج أهمها: وجود علاقة طردية قوية بين تطبيق حوكمة الشركات وتحقيق الإصلاح الإداري من وجهة نظر أفراد العينة، كما توصل إلى وجود علاقة طردية بين أبعاد الحوكمة (السلوك الأخلاقي- الإشراف والرقابة- الإفصاح والشفافية) وتحقيق الإصلاح الإداري، حيث أكدت النتائج أنّ أقوى العلاقات بين أبعاد الحوكمة والإصلاح الإداري كانت العلاقة بين بعد الإفصاح والشفافية والإصلاح الإداري، ثم العلاقة بين الإشراف والرقابة والإصلاح الإداري. بينما كانت العلاقة بين السلوك الأخلاقي والإصلاح الإداري ضعيفة وفي المرتبة الأخيرة.